A CRITICAL DISCOURSE ANALYSIS OF PRESIDENT JOKO WIDODO’S INAUGURAL SPEECH - Ayang Winda Sri Widianingsih (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
This text analysis will focus on analyzing a presidential speech, Joko Widodo in his inauguration on October, 2014. In order to gain clear explanation about the transitivity and its modality also the ideology of Joko “Jokowi” Widodo, Critical Discourse Anaysis through functional linguistic analysis will be employed. This approach is used because the analysis is intended to see its metafunction, therefore some information regarding what the process types, modality, and ideology will be scientifically proved. This metafunction analysis is based on Halliday (2004) and Fairclough (1995). It found that there are three process mostly used by the speaker such material, mental and relational. It uses material process to state what happens, many linking verbs to state what is or should be and mental process to state what speaker thinks or feels about issue. While, modality refers to a speaker’s attitudes towards or opinion about the truth of a proposition expressed by a sentence. It also extends to their attitude towards the situation or event described by a sentence. The ideology of Joko “Jokowi” Widodo exhibits pervasive use of personal pronouns. The pronouns I, and We are used pervasively in the speech than others.